Image-guided radiotherapy of the prostate using daily CBCT: the feasibility and likely benefit of implementing a margin reduction - Maund, I F (Br J Radiol, 2014)
OBJECTIVE: To investigate whether planning target volume (PTV) margins may be safely reduced in radiotherapy of localized prostate cancer incorporating daily online tube potential-cone beam CT (CBCT) image guidance and the anticipated benefit in predicted rectal toxicity. METHODS: The prostate-only clinical target volume (CTV(2)) and rectum were delineated on 1 pre-treatment CBCT each week in 18 randomly selected patients. By transposing these contours onto the original plan, dose–volume histograms (DVHs) for CTV(2) and the rectum were each calculated and combined, for each patient, to produce a single mean DVH representative of the dose delivered over the treatment course. Plans were reoptimized using reduced CTV(2) to PTV(2) margins and the consequent radiobiological impact modelled by the tumour control probability (TCP) and normal tissue complication probability (NTCP) of the rectum. RESULTS: All CBCT images were deemed of sufficient quality to identify the CTV and rectum. No loss of TCP was observed when plans using the standard 5-mm CTV(2) to PTV(2) margin of the centre were reoptimized with a 4- or 3-mm margin. Margin reduction was associated with a significant decrease in rectal NTCP (5–4 mm; p < 0.05 and 5–3 mm; p < 0.01). CONCLUSION: Using daily online image guidance with CBCT, a reduction in CTV(2) to PTV(2) margins to 3 mm is achievable without compromising tumour control. The consequent sparing of surrounding normal tissues is associated with reduced anticipated rectal toxicity. ADVANCES IN KNOWLEDGE: Margin reduction is feasible and potentially beneficial. Centres with image-guided radiotherapy capability should consider assessing whether margin reduction is possible within their institutes.